The adjustment of regional levelling network using in-house developed software - Md. Som, Zainal Abidin; Aziz, Anual (2006)
Precise levelling albeit its laborious and slowness is still serving as backbone in the establishment of height network. A regional levelling network naturally consists of several hundreds of BM points hence its adjustment is becoming a cumbersome tasks. In practice such adjustment is performed using commercial software. This paper is aim to discuss the least squares adjustment of a height network of regional coverage by using an in-house developed computer routine instead of commercial software. This paper exemplified the work done to adjust the levelling network covering the region of Sabah and Sarawak which involved quite a large number of unknown parameters with a total of about 300 BM’s in Sabah and more than 500 BM’s in Sarawak. The adjustment task has become interesting to report because it was done using as self developed in-house software. One good thing about the software is that user will find it easy to use, requires a very simple file of input data and yet manage to solve a large number of unknowns. The results indicate that the in-house software is capable in handling the adjustment of regional levelling network. Comparison of the results obtained with another adjustment results for the same data performed by commercial software (Delfy) shows that both results were very much identical.